Sincronización en américa latina (2012)
The economic integration is reflected in growing trade in goods, financial movements and foreign direct investment, events that have led to greater synchronization of business cycles worldwide. We study the economic synchronicity in Latin America following the methodology of previous literature in order to attach new evidence. The frame of reference is the Free Trade Area of the Americas (FTAA) because of its historical relevance and its possibilities beyond 2012. We conclude that although there were some important relationships, we not detected the existence of a common cycle to invite suggests the existence of full synchronization.